Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
[tex]\begin{cases}2x + 3y = 7 \\ x + y = 3 \ \ / *(-2) \end{cases}\\ \\\begin{cases}2x + 3y = 7 \\ -2x - 2y = -6\end{cases}\\+ \ ------- \\y=1\\ \\2x + 3\cdot1 = 7[/tex]
[tex]2x+3=7 \ \ |-3\\ \\ 2x+3-3=7-3\\ \\2x=4 \ \ /:2 \\ \\x=2 \\ \\ \begin{cases} x=2 \\ y=1 \end{cases}[/tex]
[tex]2x+3=7 \ \ |-3\\ \\ 2x+3-3=7-3\\ \\2x=4 \ \ /:2 \\ \\x=2 \\ \\ \begin{cases} x=2 \\ y=1 \end{cases}[/tex]
2x + 3y = 7
x + y = 3
x = 3 - y
substituting for x,
2(3 - y) + 3y = 7
= 6 - 2y + 3y = 7
6 + y = 7
thus, y = 1
x = 3 - y
= 3 - 1
= 2.
Thus, x = 2 , y = 1
Thus, (2) is correct.
x + y = 3
x = 3 - y
substituting for x,
2(3 - y) + 3y = 7
= 6 - 2y + 3y = 7
6 + y = 7
thus, y = 1
x = 3 - y
= 3 - 1
= 2.
Thus, x = 2 , y = 1
Thus, (2) is correct.
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.